(untitled) (Argos, 2025)
From a perspective of monstrousness as a transgression of canonic rules, Claudius Claudianus’ "jeweled" style is "open" enough to absorb the diverse reminiscences of Greco-Latin literary past, resulting in an exotic and frivolous work in which the tendency towards hyperbole and allegory conceals the traditional genre types beneath an artificial mask. In In Rufinum Claudianus exhibits a verbal violence and a taste for effects that are to be recognized as a prime example of baroque –and therefore monstrous– profusion.